Lime Powder Production in the Maya Puuc Region (A.D. 600–950): An Experimental Pit-Kiln. (4th March 2017) - Seligson, Kenneth; Negrón, Tomás Gallareta; Ciau, Rossana May; Bey, George J.
ABSTRACT: Powdered lime was one of the most significant materials in the daily lives of the Prehispanic Maya, yet archaeologists have uncovered relatively little evidence of production methods or locales prior to the Spanish conquest. The recent identification of a series of pit-kilns dating to the Late and Terminal Classic periods (ca.a.d. 650–950) in and around the site of Kiuic in the Puuc region of the northern lowlands of the Yucatán Peninsula provides the opportunity to investigate a sub-regional Prehispanic lime production technology. Here we present the preliminary excavation results of nine pit-kilns and then describe the experimental reconstruction and firing of a lime pit-kiln. The results indicate that the pit-kilns are more fuel-efficient than the aboveground pyres used during the post-conquest period. This in turn suggests that Prehispanic inhabitants of the Puuc managed their consumption of natural resources for producing lime during a period of sociopolitical, demographic, and environmental stresses.